The role of experience feedback channels in the continuous development of house-building platforms. Issue 2 (7th April 2015) - Jansson, Gustav; Lundkvist, Robert; Olofsson, Thomas
Abstract : Purpose: – This paper aims to describe how the experience feedback (EF) from building projects contributes to product platform development in house-building companies. House-building companies seek improvements to decrease costs, improve flow and decrease variability. Industrialised concepts using predefinitions in product platforms have provided a way of storing and reusing knowledge in project-based house-building organisations. However, the innovation in platforms is mainly incremental and based on EF from implementations in projects. Design/methodology/approach: – Qualitative data were gathered via interviews, archival studies and observations, and analysed to identify the underlying structures used to manage the incorporation of EF during platform development. Four different EF channels were studied at one Scandinavian house-builder. The data are explained using an analytical framework based on diffusion of innovation, product platforms and EF. Findings: – EF is distributed over the value chain to improve the platform over time. By using multiple channels with differing contents, it is possible to balance client demands and variation with production efficiency. Platform development using feedback channels provides opportunities for double-loop learning. Operative work on projects and the strategic decisions made by developers continuously improve the platform through a combination of knowledge pull and push. Originality/value: – A combination of different EF channels and strategies for developing knowledge pull are shown to be essential for the incremental development of product platforms in project-based house-building organisations. The development of product platforms requires a shift away from the construction industry's dominant project focus towards a more product-oriented view of house-building. Integrating the design phase with the supply chain enables variety but also creates a need for continuous platform development.